Genomic Characterization of TP53–Wild-Type Esophageal Carcinoma() - Quaas, Alexander (Transl Oncol, 2018)
Up to 40% of esophageal carcinomas have a biallelic intact TP53 gene. It is largely unclear how these carcinoma cells prevent apoptosis, what is the kind of pathway alterations, or whether therapeutically relevant alterations exist in this subgroup. We evaluated The Cancer Genome Atlas (TCGA) data to compare TP53-mutated with TP53–wild-type tumors regarding copy number variations, gene mutations, and expression patterns of protein-coding genes and miRNAs. Additionally, we analyzed up to 428 esophageal adenocarcinomas (EACs) in total using an ultra-deep parallel sequencing panel, immunohistochemistry, as well as fluorescence in situ hybridization. In the TCGA cohort, 17.3% has a biallelic intact TP53 gene. This group has a smaller average total size of somatic copy number variations. Some protein coding genes and miRNAs were differentially expressed between the TP53-wild-type and TP53-mutated group to emphasize mdm2, CCND2, TP73, or miRNA 150, 488, or 4662a. In addition, 50% of the TP53–wild-type tumors carry somatic mutations in at least one of the genes involved in the TP53 pathway. Our patient cohort revealed 41.3% TP53–wild-type tumors; 5.6% were MDM2 amplified. In accordance with the TCGA data, we did not find a prognostic relevance of TP53 in our tumor cohort as well. The mutation status of TP53 defines an important subtype in esophageal carcinoma. Our comprehensive molecular analysis revealed important and potentially therapeutically relevant genomic alterations in this subgroup.